2003
DOI: 10.1074/jbc.m305885200
|View full text |Cite
|
Sign up to set email alerts
|

HoxA10 Represses Gene Transcription in Undifferentiated Myeloid Cells by Interaction with Histone Deacetylase 2

Abstract: The homeodomain proteins, HoxA10 and Pbx1a, interact with negative cis elements to repress gene transcription in undifferentiated myeloid cells. The CYBB and NCF2 genes, which encode the gp91 PHOX

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
59
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(68 citation statements)
references
References 36 publications
8
59
1
Order By: Relevance
“…We found that CYBB and NCF2 transcription is repressed in undifferentiated myeloid cells by interaction of HoxA10, Pbx1, and HDAC2 with homologous cis-elements in these genes (24).…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…We found that CYBB and NCF2 transcription is repressed in undifferentiated myeloid cells by interaction of HoxA10, Pbx1, and HDAC2 with homologous cis-elements in these genes (24).…”
mentioning
confidence: 76%
“…Consistent with this, transcription is regulated by homologous CYBB and NCF2 ciselements that interact with a common set of transcription factors. In this study, we investigated the homologous negative cis-elements that are repressed by HoxA10 (20,21,24). Additionally, homologous positive cis-elements in the proximal promoters of these genes are activated by a multiprotein complex that includes PU.1, interferon regulatory factor-1, interferon consensus sequence-binding protein (ICSBP), and the cAMP-responsive element-binding protein-binding protein (13,45,46,51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These sequences were subcloned into the pSR␣ vector for expression in mammalian cells. HoxA10 cDNAs with mutation of the Pbx1 interaction domain were generated by PCRbased site-directed mutagenesis, by a previously described technique (19). The wild type HoxA10 was mutated to change amino acid 312 from asparagine to alanine and amino acid 313 from tryptophan to threonine (N312A/W323T HoxA10).…”
Section: Plasmids and Pcr Mutagenesismentioning
confidence: 99%
“…However, we found that HoxA10-repression of CYBB and NCF2 transcription was Pbx-independent and involved direct interaction of HoxA10 with the corepressor histone deacetylase 2 (HDAC2) (15,19). This interaction required a unique HoxA10 domain, not conserved in other Abd HoxA proteins (19). As differentiation proceeds, HoxA10 binding to the CYBB and NCF2 genes decreases, relieving repression (14,15).…”
mentioning
confidence: 91%